Intrauterine Growth Restriction and Doppler Ultrasound [Intrauterin Gelisme Geriligi ve Doppler Ultrasonografi] - Senem Arda Duz (Medicine Science, 2016)
Intrauterine growth restriction is an important perinatal problem giving rise to increased morbidity and mortality in the growth restricted fetus. Today the aim is to prevent the occurence of intrauterine growth restriction in high risk pregnancies and to deliver the fetuses already afflicted with growth restriction, before they have suffered from the effects of hypoxia. Combination of doppler ultrasound with other conventional tests of fetal well being suggests more helpful information about growth restricted fetuses. When the fetus is subjected to hypoxia, some adaptations occur in fetal circulation, so doppler ultrasound can be helpful for the clinicans about intaruterine growth restriction. [Med-Science 2016; 5(2.000): 596-605]